Systematic Literature Review On The Ontology Representation Related The Hadith Corpus - Dr. Norzulaili Mohd Ghazali; Dr. Siti Fatimah Binti Mohd Tawil (USIM Press, 2024)
Journal of Hadith Studies Volume 8 No.6 Page (105-116)